EMBR-30. A NOVEL PLK1 INHIBITOR ONVANSERTIB EFFECTIVELY SENSITIZES GROUP 3 MEDULLOBLASTOMA TO RADIOTHERAPY. (1st June 2021) - Wang, Dong; Veo, Bethany; Pierce, Angela; Foamier, Susan; Balakrishnan, Ilango; Donson, Andrew; Alimova, Irina; Erlander, Mark; Ridinger, Maya; Venkataraman, Sujatha; Vibhakar, Rajeev
Abstract: Medulloblastoma (MB) is often accompanied by MYC amplification. PLK1 is an oncogenic kinase that controls cell cycle and proliferation, and it has been preclinically validated as a cancer therapeutic target. Onvansertib (PCM-075) is a novel, orally available PLK1 inhibitor, which shows tumor growth inhibition in many types of cancer. We examined the effect of Onvansertib on MYC-driven medulloblastoma as a monotherapy or in combination with radiation. A Crisper-Cas9 screen was used to discover essential genes for MB tumor growth. Microarray and immunohistochemistry on pediatric patient samples were performed to examine the expression of PLK1. The effect of Onvansertib in vitro was measure by cell viability, colony-forming assays, extreme limiting dilution assay, and RNA-Seq. ALDH activity, cell-cycle distribution, and apoptosis were analyzed by flow cytometry. DNA damage was assessed by immunofluorescence staining. Medulloblastoma xenografts were generated to explore the monotherapy or radio-sensitizing effect. PLK1 is overexpressed in Group 3 MB. The IC50 concentrations of Onvansertib in Group 3 MB cell lines were between 4.9 and 6 nM. Onvansertib reduced colony formation, cell proliferation, stem cell renewal, and induced G2/M arrest in vitro . Moreover, Onvansertib in combination with radiation increased DNA damage and apoptosis compared with radiation alone. The combination of Onvansertib with radiotherapy resulted in marked tumor regression in orthotopic xenografts. These findings suggest that Onvansertib is an effective strategy in combination with radiotherapy in MB.